Estimation of long term streamflow generation for Sungai Yap with climate adaptation - Fatin Naqiya, Roslan (2018)
High-impact floods have become a virtually annual experience in Malaysia, yet flood insurance has remained a grossly neglected part of comprehensive integrated flood risk management. To more efficiently use the limited amount of water under the changing world or to resourcefully provide adequate time for flood warning, this issue has seeking advanced techniques to improve an efficiency of streamflow forecasting for the short-term and long-term basis. This study is to develop the streamflow equation for the long-term streamflow generation at Sungai Yap using Identification of Unit Hydrograph and Component flow from Rainfall, Evaporation and Streamflow (IHACRES) model. The calibration and validation results show high correlation value (0.921) with low ARPE (-0.102). Based on this analysis, about 6 importance parameters have been identified in developing the streamflow generation with considered the climate assessment. The outcome is very significant for the efficient management of the river flow in the future year. It is also can be as a significant data input that must be considered for the long term urban planning and water resources at this area.